CFHTLenS: Higher-order galaxy-mass correlations probed by galaxy-galaxy-galaxy lensing - Simon, P; Erben, T; Schneider, P; Heymans, C; Hildebrandt, H; Hoekstra, H; Kitching, T; Mellier, Y; Miller, L; Waerbeke, L; Bonnett, C; Coupon, J; et al. (2013)
We present the first direct measurement of the galaxy-matter bispectrum as a function of galaxy luminosity, stellar mass, and SED type. Our analysis uses a galaxy-galaxy-galaxy lensing technique (G3L), on angular scales between 9 arcsec to 50 arcmin, to quantify (i) the excess surface mass density around galaxy pairs (excess mass hereafter) and (ii) the excess shear-shear correlations around single galaxies, both of which yield a measure of two types of galaxy-matter bispectra. We apply our method to the state-of-the-art Canada-France-Hawaii Telescope Lensing Survey (CFHTLenS), spanning 154 square degrees. This survey allows us to detect a significant change of the bispectra with lens properties. Measurements for lens populations with distinct redshift distributions become comparable by a newly devised normalisation technique. That will also aid future comparisons to other surveys or simulations. A significant dependence of the normalised G3L statistics on luminosity within -23